Essentials of marketing - Charles, W. Lamb, Jr. (Thomson Learning, 2006)
This book is aimed at undergraduates taking an introductory marketing course. Essentials of Marketing provides an overview of the techniques, supporting theories and tactical decision-making processes involved in marketing. As well as traditional marketing techniques, up-to-date topics such as green issues, post-modern thinking, relationship marketing and ethics are also covered. The 4th edition has been thoroughly re-written to include the new 7 C's framework The language is concise and transparent making this book an enjoyable read for students. A new full colour layout also helps to engage the reader